Co-movement and causal relationships between conventional and Islamic stock~market returns under regime-switching framework - Fatma Mathlouthi; Slah Bahloul (Journal of Capital Markets Studies (JCMS), 2022)
Purpose This paper aims at examining the co-movement dependent regime and causality relationships between conventional and Islamic returns for emerging, frontier and developed markets from November 2008 to August 2020. Design/methodology/approach First, the authors used the Markov-switching autoregression (MS-AR) model to capture the regime-switching behavior in the stock market returns. Second, the authors applied the Markov-switching regression and vector autoregression (MS-VAR) models in order to study, respectively, the co-movement and causality relationship between returns of conventional and Islamic indexes across market states. Findings Results show the presence of two different regimes for the three studied markets, namely, stability and crisis periods. Also, the authors found evidence of a co-movement relationship between the conventional and Islamic indexes for the three studied markets whatever the regime. For the Granger causality, it is proved only for emerging and developed markets and only during the stability regime. Finally, the authors conclude that Islamic indexes can act as diversifiers, or safe-haven assets are not strongly supported. Originality/value This paper is the first study that examines the co-movement and the causal relationship between conventional and Islamic indexes not only across different financial markets' regimes but also during the COVID-19 period. The findings may help investors in making educated decisions about whether or not to add Islamic indexes to their portfolios especially during the recent outbreak.
Keywords: G01; G11; G15; 330; Conventional index; Emerging markets; Frontier markets; Islamic index; Markov-switching regressions; MS-VAR model